Improving Students’ Figurative Language Writing through Explicit Instruction - Ningrum, Nilam Nur Widya; Agustina, Sheila (Indonesian Journal of Education Methods Development, 2025)
General Background: Writing in English requires mastery of lexical, compositional, and stylistic components, making it a complex skill for learners to acquire. Specific Background: Many junior high school students struggle with writing due to limited vocabulary and lack of engagement with creative language use. Knowledge Gap: While explicit instruction has been widely used to teach various language skills, its application in developing students’ use of figurative language in writing remains underexplored, particularly at the junior high school level. Aims: This study investigates how explicit instruction in figurative language contributes to improving students’ writing skills. Results: Using a pre-experimental design with 30 eighth-grade students in Sidoarjo, the study recorded an increase in mean scores from 59.5 (pre-test) to 70.67 (post-test), supported by t-test results, indicating statistically significant improvement. Novelty: This research integrates explicit instruction with figurative language teaching, offering a structured approach that enhances both linguistic creativity and writing quality. Implications: The findings suggest that explicit instruction can be a practical strategy for helping students develop stronger, more expressive writing skills, and promote independent application of language in academic and real-life contexts. Highlights : Uses pre-experimental design to measure writing skill development Focuses on eighth-grade students in a real classroom context Emphasizes the role of explicit instruction in creative writing Keywords : Explicit Instruction, Figurative Language, Writing Skills, Junior High School, Language Education